CORRELATION ANALYSIS OF HOUSEHOLD DEMAND FACTORS WITH THE DEMAND FOR CHICKEN MEAT IN THE RAWA INDAH MARKET, BONTANG MUNICIPALITY - Anisa Ambarwati; Edy Prasetyo; Wahyu Dyah Prastiwi (Jurnal Hexagro, 2024)
The fluctuations in the demand for broiler meat in various places are different. Demand is relatedto price, income, number of family members, tastes, and location. The study aimed to analyze therelationship between demand factors, which include cost, income, number of family members,appetite, and location, with the demand for broiler meat at Rawa Indah Market, Bontang Municipality.The research was conducted in March - April 2022 at the Rawa Indah Market, Bontang City usinga survey method and standardized chicken meat consumers as respondents. Rawa Indah Market,Bontang Municipality, was chosen purposively as the research location because it is the primary market.Determining the number of samples using the calculation of the Cochran formula as many as 70respondents with the determination of respondents by accidental sampling with the criteria ofBontang Municipality residents who are shopping aged 18-64 years. The data used in this study areprimary data collected from interviews with consumers in the market using preparedquestionnaires and secondary data collected from BPS Bontang Municipality, East Kalimantan. The dataobtained were analyzed descriptively and quantitatively using Spearman's Rank test analysiswith independent variables including price, income, number of consumers' family members,tastes, and location, as well as the dependent variable is the amount of demand for broiler chickenmeat. The results showed that price, income, number of family members, tastes, and locationcorrelated weakly with the demand for broiler meat in Bontang Municipality.